SYNTHESIS OF DIGITAL NONLINEAR ROBUST CONTROL OF MULTICHANNEL SYSTEMS - Nikitina, T. B. (Radio Electronics, Computer Science, Control, 2024)
A method of synthesis for robust control multichannel systems, workings on rough and exact control principle in accordance with iteration algorithm is developed. The example of dynamic descriptions for synthesized twochannel electromechanical system is resulted.